2002
DOI: 10.1046/j.1439-037x.2002.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Moisture Deficit on Forage Quality, Digestibility, and Protein Fractionation of Kura Clover

Abstract: Kura clover (Trifolium ambiguum M.B.) is a persistent rhizomatous forage legume with great potential for permanent pastures. The effects of a soil moisture deficit on forage quality, digestibility and protein fractionation of two cultivars of Kura clover (Endura and Rhizo) were investigated in this study for 1 year. The responses of alfalfa (Medicago sativa L.) and red clover (Trifolium pratense L.) were also characterized. Stands of each species were field-grown and submitted to two soil water regimes promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
(38 reference statements)
4
21
4
Order By: Relevance
“…However, cultivars tested in that study (Endura and Rhizo) were different from those evaluated in the present study. The chemical composition for the two Kura clover cultivars in the present study are in good agreement with the literature values previously reported for various Kura clover cultivars (Allinson et al 1985;Sheaffer and Marten 1991;Sleugh et al 2000;Seguin et al 2002).…”
Section: Chemical Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, cultivars tested in that study (Endura and Rhizo) were different from those evaluated in the present study. The chemical composition for the two Kura clover cultivars in the present study are in good agreement with the literature values previously reported for various Kura clover cultivars (Allinson et al 1985;Sheaffer and Marten 1991;Sleugh et al 2000;Seguin et al 2002).…”
Section: Chemical Compositionsupporting
confidence: 92%
“…Results are in accordance with those of Seguin et al (2002) who found no differences in protein fractions between Endura and Rhizo Kura clover cultivars. Protein fractions of Kura clover were however, significantly affected by ensiling (Table 3).…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…() and Seguin et al. () found a minor effect of drought stress on protein content. Our studies showed a small (statistically unproven) increase in CP content under drought, both in alfalfa and Festulolium .…”
Section: Discussionmentioning
confidence: 94%
“…In decomposition studies, proximate analyses are commonly used to determine plant material composition (Quemada and Cabrera 1995;Henriksen and Breland 1999;Gunnarsson and Marstorp 2002;Seguin et al 2002;Henriksen et al 2007). A widely used proximate analysis is the neutral detergent solution (NDF)/acid detergent solution (ADF) method (Goering and van Soest 1970) with which plant materials are extracted under reflux successively with a NDF and an ADF.…”
Section: Introductionmentioning
confidence: 99%